New legislative provisions in the context of responding to the reality of start-ups in Algeria - Bouhelais, Ilhem; BENISSAD, Adra (Journal of Human Sciences, 2025)
The Algerian legislator established a set of legislative provisions with the aim of establishing a suitable environment for start-ups. in this study, we wanted to ask about the most important of these legislative provisions and their importance in supporting start-ups. In this context, the legislator established the system of paticipatory financing as a new form of financing and the system of venture capital companies. This is in addition to setting special provisions in the public procurement law and in commercial law,In addition to regulating new professions within banking law. Through this study, we have determined that there is a real will to support these institutions. However, continuing efforts in this framwork and activating these legislative provisions in practical reality remains a necessary matter to achieve the desired economic goal.